Renal disease in pregnancy. (April 2023) - Wiles, Kate; Skinner, Laura; Smith, Priscilla
Abstract: The diagnosis of acute kidney injury (AKI) in pregnancy is complicated by haemodynamic and urinary tract changes in pregnancy, and non-pregnant references intervals for serum creatinine should not be used. Pre-eclampsia is the most common cause of AKI in pregnancy. Although pregnancy-associated haemolytic microangiopathies are rare, it is useful for physicians and nephrologists to be aware of potential clinical discriminators as different, timely management is required. Pregnancy is successful for most women and pregnant individuals with chronic kidney disease (CKD). There is, however, an increased risk of adverse parental and neonatal outcomes at all stages of CKD, including pre-eclampsia, growth restriction, preterm delivery, low birthweight, neonatal unit admission and postpartum loss of parental kidney function. Pregnant persons with CKD should therefore have access to pre-pregnancy counselling to be able to make an informed decision about proceeding with pregnancy. A multidisciplinary team with expertise in obstetric nephrology should coordinate the care of pregnant individuals with CKD, which includes obstetric and kidney disease surveillance, monitoring of immunosuppression, and the initiation and/or intensification of haemodialysis if required. The diagnosis of superimposed pre-eclampsia remains clinically challenging.